Hubungan Dukungan Sosial dengan Psychological Well-Being pada Mahasiswa yang Sedang Mengerjakan - Tambunan, Jeressa Amadina; Sulistiasih, Sulistiasih (Guidance : Jurnal Bimbingan dan Konseling, 2024)
Students are often urged to pass in a timely manner, while also preparing for the final task for a bachelor’s thesis, as well as preparation in a career that students will face after graduation. All the demands that come from various parties and tasks that exist until the end of the course, quite make many students feel less well-being in their lives. The purpose of this study is to find out if there is a significant relationship between some types of social support and psychological well-being in college students who are undergoing their studies. The methods used in this study are quantitative methods, with correlational research types, with nonprobability sampling techniques. The population in this study is students/I years of the 2018 Force and 2019 University of Bhayangkara in Greater Jakarta. The results of this study were that the Alternative Hypothesis (HA) in this study was accepted with the results of the social support variable correlation coefficient having a positive strong relationship with the psychological well-being variable.